O ESTADO DEMIURGO: Alberto Torres e a construção nacional - Bariani, Edison (Caderno CRH, 2007)
Espécie de precursor, no Brasil, de uma modalidade de institution building, Alberto Torres – cético em relação à habilidade e possibilidade de ação de outros agentes – projetou o Estado como construtor da Nação e organizador da sociedade brasileira, essa ainda, segundo ele, informe, dado o processo de transplantação que a teria iniciado. PALAVRAS-CHAVE: Alberto Torres, Estado, nacionalismo. THE DIVINE STATE: Alberto Torres and the national construction Edison Bariani A kind of pioneer in Brazil of a modality of institution building, Alberto Torres – sceptic about the ability and possibility of action by other agents – projected the State as the constructor of the Nation and organizer of Brazilian society, yet – by the author – formless because of the transplantation process that started it. KEYWORDS: Alberto Torres, State, nationalism. L’ ETAT DEMIURGIQUE: Alberto Torres et la construction nationale Edison Bariani En tant que précurseur d’une modalité d’institution building au Brésil, Alberto Torres – sceptique quant à l’habileté et à la possibilité d’action d’autres agents – a planifié l’Etat comme constructeur de la Nation et comme organisateur de la société brésilienne, celle-ci – selon lui – considérant en cours le processus de transplantation qui l’aurait initiée. MOTS-CLÉS: Alberto Torres, Etat, nationalisme. Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br